2006
DOI: 10.1152/jn.01138.2005
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of an Avian Basal Ganglia Circuit Prevent Context-Dependent Changes to Song Variability

Abstract: Trial-by-trial variability is important in feedback-based motor learning. Variation in motor output enables evaluation mechanisms to differentially reinforce patterns of motor activity that produce desired behaviors. Here, we studied neural substrates of variability in the performance of adult birdsong, a complex, learned motor skill used for courtship. Song performance is more variable when male birds sing alone (undirected) than when they sing to females (directed). We test the role of the anterior forebrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
397
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(443 citation statements)
references
References 44 publications
35
397
8
Order By: Relevance
“…lesion and postlesion directed song from 4 birds (see Materials and Methods) and analyzed pitch variability. Consistent with prior results (Kao et al, 2005;Kao and Brainard, 2006;Sakata et al, 2008), we found a lower pitch SD in prelesion directed versus undirected song ( p Ͻ 0.05, Wilcoxon signed-rank test; prelesion directed SD: mean 0.36 semitones, range 0.17-0.64 semitones; prelesion undirected: 0.47, 0.23-0.98). Interestingly, we did not find differences in either prelesion versus postlesion directed pitch SD or prelesion versus postlesion undirected pitch SD ( p Ͼ 0.05, Wilcoxon signed-rank tests).…”
Section: Resultssupporting
confidence: 92%
“…lesion and postlesion directed song from 4 birds (see Materials and Methods) and analyzed pitch variability. Consistent with prior results (Kao et al, 2005;Kao and Brainard, 2006;Sakata et al, 2008), we found a lower pitch SD in prelesion directed versus undirected song ( p Ͻ 0.05, Wilcoxon signed-rank test; prelesion directed SD: mean 0.36 semitones, range 0.17-0.64 semitones; prelesion undirected: 0.47, 0.23-0.98). Interestingly, we did not find differences in either prelesion versus postlesion directed pitch SD or prelesion versus postlesion undirected pitch SD ( p Ͼ 0.05, Wilcoxon signed-rank tests).…”
Section: Resultssupporting
confidence: 92%
“…Analyses in other papers indicate that pitch can vary by 1-3% (0.1-0.4 octaves) (Kao and Brainard 2006), while duration can vary by 1-4% (Cooper and Goller 2006;Glaze and Troyer 2006). Variation within the normal range for individual birds should not affect the bird's classification of an individual's song in an operant classification task, whereas variation beyond that range might or might not, depending on the importance of the parameter to recognition and classification.…”
Section: Song Manipulationsmentioning
confidence: 96%
“…We shifted the pitch of songs from each male by Ϯ 0, 0.01, 0.03, 0.06, 0.11, 0.21, 0.40, and 0.71 octaves, equal to multiplying and dividing the frequency by 100, 101, 102, 104, 108, 116, 132, and 164%. This logarithmic series of shifts was chosen to span and exceed the range of natural variability in note pitch; the pitch of individual notes has been shown to vary by 1-3% of their fundamental frequency, in undirected song (Kao and Brainard 2006). As illustrated in Fig.…”
Section: Classification Of Pitch-shifted Songsmentioning
confidence: 99%
See 2 more Smart Citations